An Application of an Initial Full Value of Vaccine Assessment Methodology to Measles-Rubella MAPs for Use in Low- and Middle-Income Countries - Melissa Ko; Collrane Frivold; Mercy Mvundura; Adam Soble; Christopher Gregory; Hans Christiansen; Mateusz Hasso-Agopsowicz; Han Fu; Mark Jit; Shan Hsu; Jessica Joyce Mistilis; Tiziana Scarna; et al. (Vaccines)
Measles and rubella micro-array patches (MR-MAPs) are a promising innovation to address limitations of the current needle and syringe (N&S) presentation due to their single-dose presentation, ease of use, and improved thermostability. To direct and accelerate further research and interventions, an initial full value vaccine assessment (iFVVA) was initiated prior to MR-MAPs entering phase I trials to quantify their value and identify key data gaps and challenges. The iFVVA utilized a mixed-methods approach with rapid assessment of literature, stakeholder interviews and surveys, and quantitative data analyses to (i) assess global need for improved MR vaccines and how MR-MAPs could address MR problem statements; (ii) estimate costs and benefits of MR-MAPs; (iii) identify the best pathway from development to delivery; and (iv) identify outstanding areas of need where stakeholder intervention can be helpful. These analyses found that if MR-MAPs are broadly deployed, they can potentially reach an additional 80 million children compared to the N&S presentation between 2030–2040. MR-MAPs can avert up to 37 million measles cases, 400,000 measles deaths, and 26 million disability-adjusted life years (DALYs). MR-MAPs with the most optimal product characteristics of low price, controlled temperature chain (CTC) properties, and small cold chain volumes were shown to be cost saving for routine immunization (RI) in low- and middle-income countries (LMICs) compared to N&S. Uncertainties about price and future vaccine coverage impact the potential cost-effectiveness of introducing MR-MAPs in LMICs, indicating that it could be cost-effective in 16–81% of LMICs. Furthermore, this iFVVA highlighted the importance of upfront donor investment in manufacturing set-up and clinical studies and the critical influence of an appropriate price to ensure country and manufacturer financial sustainability. To ensure that MR-MAPs achieve the greatest public health benefit, MAP developers, vaccine manufacturers, donors, financiers, and policy- and decision-makers will need close collaboration and open communications.